Ripple torque minimization in six-phase PM generators with arbitrary EMF waveform - Catuogno, Guillermo Ricardo (2016)
A new strategy is proposed to control the power flow in Six-Phase Permanent Magnet Generators (SPPMG) with arbitrary Electromotive Force (EMF) waveform. The strategy aims to minimize ripple torque and reduce reactive power that flow on the machine. The control algorithm is based on the instantaneous active and reactive power theory and is implemented with two conventional three-phase converters with current control loops. The control currents of the machine are implemented using a variable change, allowing for any SPPMG with arbitrary EMF waveform get a similar result that a vector control with sinusoidal EMF waveform.